2017
DOI: 10.1371/journal.pone.0172392
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing antiretroviral treatment suboptimal adherence among perinatally HIV-infected adolescents in Thailand

Abstract: BackgroundExisting studies have suggested decreased adherence and rebound in mortality in perinatally HIV-infected adolescents receiving antiretroviral therapy (ART) as compared to adults and young children.MethodsWe used both quantitative and qualitative approaches to identify factors influencing adherence among perinatally infected adolescents in Thailand. We analyzed data from 568 pairs of perinatally infected adolescents (aged 12–19) and their primary caregivers in the Teens Living With Antiretrovirals (TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 41 publications
4
58
0
7
Order By: Relevance
“…Firstly, the fear of social ostracization, resulting from greater awareness of the stigmatization around HIV in late adolescence, could negatively impact attendance at an ART centre [21]. Secondly, this period is associated with sexual debut for some adolescents; [7] apprehension about inadvertent partner disclosure, if seen at the ART centre, along with reduced adult supervision, could further limit follow-up [22]. Lastly, the transition into adulthood may be associated with greater familial responsibilities for some adolescents, relegating personal health to a secondary priority [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the fear of social ostracization, resulting from greater awareness of the stigmatization around HIV in late adolescence, could negatively impact attendance at an ART centre [21]. Secondly, this period is associated with sexual debut for some adolescents; [7] apprehension about inadvertent partner disclosure, if seen at the ART centre, along with reduced adult supervision, could further limit follow-up [22]. Lastly, the transition into adulthood may be associated with greater familial responsibilities for some adolescents, relegating personal health to a secondary priority [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown that with the advances in effectiveness and availability of cART, HIV infected children are now surviving to adolescence and emerging as a new group in the global HIV/AIDS pandemic [24]. It has been also cited that despite the fact that HIV positive adolescents find it a challenge living with the HIV, they have remained positive and focused with their education [24].…”
Section: Socio-demographic Characteristics Of the Samplementioning
confidence: 99%
“…In other reports, the overall level of comprehensive correct knowledge of HIV and AIDS remains very low among older adolescents aged 15 -19 [23]. However some studies found that HIV-infected adolescents demonstrated good knowledge regarding HIV/AIDS and cART, including the consequences of developing drug resistance with suboptimal cART adherence [24]. Despite some reports that HIV positive adolescents have good knowledge regarding HIV/AIDS progression, non-adherence to cART and treatment failure have remained prevalent in this age group.…”
Section: Introductionmentioning
confidence: 99%
“…Additional barriers to VLS in adolescents include drug toxicity and intolerance, psychological problems (depression, anxiety, and trauma) and social barriers, including stigma, have been linked to poor treatment adherence in adolescents and young adults. [57][58][59][60] Important limitations of the study are that genotyping results after first-line ART failure were not always available in realtime to health care providers for the optimization of ART before switching to second-line regimens. In addition, limited adherence and ATV/r as second-line ART may have reduced the rate of VS 50 .…”
Section: Discussionmentioning
confidence: 99%